Comparing the Current Training Running Demands of Elite Camogie Players to Competitive Match-Play - Philip Connors; Declan Browne; Des Earls; Paula Fitzpatrick; Paula Rankin (MDPI AG, 2022)
Training to meet match-play demands is a primary objective in an athlete's preparation for their games. Despite camogie match-play running demands being available, how current training practices compare, specifically individual training components, remains unknown. This study aimed to investigate and compare current elite camogie training to match-play demands. Thirty-three (n = 33) elite camogie players wore 10 Hz Playertek GPS units during twenty-five training sessions and ten competitive matches. Training sessions were analysed using ball-in-play time and split into warm-ups, drills, small-sided games, running, and training matches. Metrics were converted into relative terms (per minute), to allow comparisons. Players cover significantly greater (p < 0.05) total distance (non-parametric standardised effect sizes (r = 0.45)), peak speed (r = 0.45), high-speed running (r = 0.13), sprint distance (r = 0.20), and total decelerations (r = 0.12-0.22) during match-play than training. Relatively, players cover significantly greater distance during running, small-sided games, and training matches compared to match-play (r = 0.21-0.29). Compared with match-play, running results in significantly greater high-speed running and sprint distance (r = 0.18-0.41), with greater accelerations (3-4 m∙s−2) during warm-ups, running, and small-sided games (r = 0.14-0.28). Current total training demands seem to fall behind match-play. However, relatively, training matches and small-sided games match or surpass competitive match-play demands. These findings may be utilised in preparing camogie teams for competition.